Allora & Calzadilla - Specters of noon - White, Michelle 1979-; Tejada, Roberto 1964-; Ault, Julie 1957-; DeLoughrey, Elizabeth M. 1967-; Immerwahr, Daniel 1980-; Lang, David 1957-; Mosquera, Gerardo 1945-; Nesbit, Molly 1952-; Ramírez, Mari Carmen 1955-; Stavrinaki, Maria (The Menil Collection, 2021)
The Puerto Rico-based collaborative duo Allora & Calzadilla created Specters of Noon as a group of seven large-scale works specifically for the Menil Collection. Orchestrated around the idea of Solar Noon, a notion derived from Surrealist texts by Roger Caillois, Aime Cesaire, and others that probe the transcultural mythology of noon-the time of day when shadows disappear and delirious visions momentarily reign-the works include light projections, guano, ship engines, live vocal performance, and coal. Using the Menil's Surrealist holdings as a point of departure, Specters of Noon is infused throughout with a Caribbean perspective that addresses the instability of environmental and colonial politics; one work is a massive power transformer damaged in Hurricane Maria that is half-sheathed in brass. Filled with stunning installation photography and insightful texts both commissioned and reprinted, this volume captures the spirit of Jennifer Allora (b. 1974) and Guillermo Calzadilla's (b. 1971) deeply researched and multifaceted work. Exhibition: Menil Collection, Houston, USA (26.09.2020-20.26.2021)
Impressum: "Allora & Calzadilla: Specters of Noon" is organized by the Menil Collection, Houston. Curated by Michelle White, September 26, 2020-June 20, 2021
Keywords: Allora & Calzadilla; Installation -- Kunst; Ausstellungskatalog -- The Menil Collection -- 26.09.2020-20.06.2021 -- Houston, Tex.